Redefinition of Steriphodon Abeille de Perrin, 1895 (Coleoptera: Anthicidae), with a new species description, checklist, and key to species - Telnov, Dmitry (Zootaxa, 2021)
Steriphodon Abeille de Perrin, 1895, a small genus of Eurygeniinae (Anthicidae) is reviewed. Critical morphology of the genus is reassessed and discussed. An annotated checklist, key to species and new records are provided. Steriphodon ottomerkli sp. nov. from the Balochistan Province, Pakistan is described and illustrated.